THE PLACE OF DORTASH CULTURAL HERITAGE IN HISTORY (Scientific Conference on Multidisciplinary Studies, 2025)
The archaeological site of Dortash, which dates back to the 1st millennium BC, has been protected by the state due to its antiquity. In a unique location at the foot of the Bandikhan mountain, which connects Kadim Chaganiyon with Maverunnahr, there was a Friday market where people would gather.